Understanding the experiences of working mothers in financial services toward family supportive practices - Gamiet, Aniekah (Organisational Psychology, 2018)
This study sought to understand the experiences of working mothers regarding the family supportive policies and practices offered within a financial services company in Cape Town. The financial services sector in South Africa is still regarded as male dominated. The results from 17 in-depth semi structured interviews conducted with full-time employed mothers from diverse demographic and professional backgrounds were analysed using thematic analysis. The mothers generally experienced the organisation as supportive of their dual work and family commitments. Specifically, flexibility and supportive supervisors were the most important forms of family supportive practices that helped them balance their work and family responsibilities, though many mothers expressed the need for alternative family leave benefits. Interestingly socio-cultural factors appeared to play an influential role in the mothers' experiences of the organisation's family supportive policies and practices. Management implications for the attraction and retention of skilled mothers in the finance sector are discussed.